REVENGE PORN IN INDONESIAN LAW: AN ANALYSIS OF CRIMINAL LIABILITY AND VICTIM PROTECTION BASED ON THE ELECTRONIC INFORMATION AND TRANSACTIONS LAW AND THE SEXUAL VIOLENCE CRIME LAW - Madani, Irfan Syauqi; Firmansyah, Hery (Awang Long Law Review, 2025)
The advancement of information technology has led to new forms of crime, one of which is revenge porn. This crime involves the non-consensual distribution of intimate content, often carried out as retaliation after a failed relationship. Although Indonesian law has addressed this issue, victim protection remains insufficient and fragmented. This research aims to analyze the criminal liability of perpetrators and the legal protection for revenge porn victims in Indonesia under the Electronic Information and Transactions Law and the Sexual Violence Crime Law. The study employs a normative juridical method with a case study approach. Findings indicate that while the Electronic Information and Transactions Law can criminalize perpetrators, it falls short in addressing victims' psychological and social harm. The Sexual Violence Crime Law provides more comprehensive protection, including restitution and recovery services. However, implementation faces challenges such as societal stigma and a lack of gender-sensitive law enforcement. Thus, an integrated approach involving regulation, law enforcement, and public education is crucial to ensure holistic victim protection. In conclusion, the state must strengthen victim-centered legal implementation and consider immaterial impacts, while promoting prevention through legal reform and public awareness.